2022
DOI: 10.3389/fonc.2022.970367
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of m6A RNA methylation regulators, PD-L1 and immune infiltrates in gastric cancer

Abstract: Gastric cancer is the fourth most frequent cancer and has a high death rate. Immunotherapy represented by PD-1 has brought hope for the treatment of advanced gastric cancer. Methylation of the m6A genes is linked to the onset and progression of numerous cancers, but there are few studies on gastric cancer. The main purpose of this study aims to analyze the relationship between m6A RNA methylation regulators, PD-L1, prognosis and tumor immune microenvironment (TIME) in gastric cancer. The Cancer Genome Atlas (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Immune evasion: METTL3-mediated RNA modification may also play a role in immune evasion by regulating exons. 33 The present meta-analysis involved seven studies and revealed that a high expression level of METTL3 is associated with a poor OS in GC patients. This study has demonstrated that high METTL3 expression was associated with significantly poorer OS (HR = 2.37, 95% CI 1.66-3.39, P < 0.01) and unfavorable DFS (HR = 2.58, 95% CI 1.97-3.38, P < 0.01), as did unfavorable PFS (HR = 1.48, 95% CI 1.19-1.84, P < 0.01)/RFS (HR = 2.62, 95% CI 1.93-5.62, P < 0.01)/PPS (HR = 1.53, 95% CI 1.22-1.91, P < 0.01).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Immune evasion: METTL3-mediated RNA modification may also play a role in immune evasion by regulating exons. 33 The present meta-analysis involved seven studies and revealed that a high expression level of METTL3 is associated with a poor OS in GC patients. This study has demonstrated that high METTL3 expression was associated with significantly poorer OS (HR = 2.37, 95% CI 1.66-3.39, P < 0.01) and unfavorable DFS (HR = 2.58, 95% CI 1.97-3.38, P < 0.01), as did unfavorable PFS (HR = 1.48, 95% CI 1.19-1.84, P < 0.01)/RFS (HR = 2.62, 95% CI 1.93-5.62, P < 0.01)/PPS (HR = 1.53, 95% CI 1.22-1.91, P < 0.01).…”
Section: Discussionmentioning
confidence: 92%
“…Immune evasion: METTL3-mediated RNA modification may also play a role in immune evasion by regulating exons. 33…”
Section: Discussionmentioning
confidence: 99%
“…We identified HNRNPC as a hub gene that interacts with m6A methylation via immune processes and can effectively classify IMSs. Some studies found an association between HNRNPC and tumor progression, 46 , 47 , 48 as well as immune cell infiltration. 49 However, which immune cells can be regulated by HNRNPC , thus remodeling the TME is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found an association between HNRNPC and tumor progression, [46][47][48] as well as immune cell infiltration. 49 However, which immune cells can be regulated by HNRNPC, thus remodeling the TME is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There are 172 identified forms of RNA alterations, and the most common chemical modifications are m6A, m1A, and m5C. m6A is one of the most prevalent eukaryotic mRNA modifications ( 8 ). The m6A modification involves the methylation of adenosine’s sixth nitrogen atom, with Sadenosylmethionine, a cellular methyltransferase substrate, functioning as the methyl donor ( 9 ).…”
Section: Introductionmentioning
confidence: 99%